A Rare Case Report of Thoracic Ectopia Cordis: An Obstetrician’s Point of View in Multidisciplinary Approach - Diana Ramasauskaite; Vilija Snieckuviene; Viktorija Zitkute; Ramune Vankeviciene; Dalia Lauzikiene; Grazina Drasutiene (Case Reports in Pediatrics)
Ectopia cordis is a rare congenital anomaly associated with the heart positioned outside of the thoracic cavity either partially or completely. It can be associated with other congenital abnormalities. Overall, the prognosis for infants with ectopia cordis is very poor but depends greatly on the type and severity of ectopia cordis and intracardiac and associated malformations. We present one case of a fetus with prenatally diagnosed thoracic ectopia cordis with intracardiac defects and omphalocele, all the abnormalities seen in pentalogy of Cantrell except a diaphragmatic defect. Considering poor prognosis for fetus, conservative management of prenatal care has been chosen. At the 42nd gestational week, during the active stage of labor, due to fetal distress, cesarean section was performed at a tertiary level hospital. The condition of the infant was impairing rapidly and the newborn succumbed within 24 hours. We discuss the perinatal care concerning this rare anomaly.